2017
DOI: 10.3847/1538-4357/834/1/58
|View full text |Cite
|
Sign up to set email alerts
|

On the Survival of High-Altitude Open Clusters Within the Milky Way Galaxy Tides

Abstract: It is a common assumption that high-altitude open clusters live longer compared with clusters moving close to the Galactic plane. This is because at high altitudes, open clusters are far from the disruptive effects of in-plane substructures, such as spiral arms, molecular clouds and the bar. However, an important aspect to consider in this scenario is that orbits of high-altitude open clusters will eventually cross the Galactic plane, where the vertical tidal field of the disk is strong. In this work we simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…This quickly depletes this family of orbits such that Rossi and Hurley (2015a) suggested that such clusters should be rare. Martinez-Medina et al (2017) showed that tidal compression generated by local cores in the overlapping potentials of the bar and spiral arms (i.e. mainly at the tips of the bar) play a protective role on clusters (see also , for considerations on cluster formation in these areas).…”
Section: In Non-axisymmetric Barred Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This quickly depletes this family of orbits such that Rossi and Hurley (2015a) suggested that such clusters should be rare. Martinez-Medina et al (2017) showed that tidal compression generated by local cores in the overlapping potentials of the bar and spiral arms (i.e. mainly at the tips of the bar) play a protective role on clusters (see also , for considerations on cluster formation in these areas).…”
Section: In Non-axisymmetric Barred Potentialsmentioning
confidence: 99%
“…By varying the orbital inclination, Martinez-Medina et al (2017) showed, on the one hand, that clusters with a low maximum orbital latitude (i.e. staying near the disc) cross the disc at a lower speed than those on a more inclined orbit.…”
Section: Disc Crossingmentioning
confidence: 99%
See 1 more Smart Citation
“…The clusters addressed in this work are generally believed to be old and far from the Galactic plane. At first glance, this is surprising because the survival time of such clusters is lower than their thin disk counterparts (Martinez-Medina et al 2017). A simple model where most star formation happens in the thin disk has to be updated to explain open clusters at high galactic latitudes, assuming these are real 1 .…”
Section: Introductionmentioning
confidence: 99%
“…As clusters age, the expulsion of gas by stellar feedback as well as dynamical interactions between stars and binary systems in the cluster soften its gravitational potential, leading to their expansion and to their partial or total dissolution into the field of their host galaxy (e.g., Spitzer & Harm 1958;Parker & Meyer 2012;Parker & Dale 2013;Dib et al 2011a,b;Dib 2011;Dib et al 2013;Pfalzner & Kaczmarek 2013;Brinkmann et al 2017). Clusters can also be ⋆ E-mail, SD: sami.dib@gmail.com † Royal Society Dorothy Hodgkin Fellow disrupted by close encounters with giant molecular clouds as they orbit the Galactic centre (e.g., Gieles et al 2006) or by being subjected to strong tidal fields (e.g., Dalessandro et al 2015;Zhai et al 2017;Martinez-Medina et al 2017). …”
Section: Introductionmentioning
confidence: 99%